THE STRATEGY OF AN ISLAMIC BOARDING SCHOOL OF PANGERAN DIPONEGORO IN YOGYAKARTA TO PRESERVE ITS EXISTENCE THROUGH CHARACTER EDUCATION BUILDING TOWARD STUDENTS - Choirul Muna; Fajar Sodik (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2021)
Nowadays, the issue of character education is spreading, given thevarious events that have occurred, so that the determination of the youthof this country has fallen so sharply. This study aims to analyze thestrategy of the Prince Diponegoro Islamic Boarding School inYogyakarta in maintaining its existence through the cultivation ofcharacter education for students. This type of research is a type ofqualitative research. The results of this study are the Prince DiponegoroIslamic Boarding School, Yogyakarta, managed to maintain its existencein the midst of the presence of modern education. The Islamic boardingschool through its educational programs with existing methods is able tocontinue to exist. The strategies implemented such as the exemplarymethod, the habituation method, the mau`izhah method or advice as wellas the motivation and intimidation method were considered optimal andable to change the character of the santri for the better. so that manyguardians of students believe and leave their children in the boardingschool.